In praise of conscious awareness: a new framework for the investigation of “continuous improvement” in expert athletes - Toner, John; Moran, Aidan (Frontiers in Psychology, 2014)
A key postulate of traditional theories of motor skill learning (e.g., Fitts and Posner, 1967; Shiffrin and Schneider, 1977) is that expert performance is largely automatic in nature and tends to deteriorate when the performer ‘reinvests’ in, or attempts to exert conscious control over, proceduralized movements (Masters and Maxwell, 2008). This postulate is challenged, however, by recent empirical evidence (e.g., Nyberg, in press; Geeves et al., in press) which shows that conscious cognitive activity plays a key role in facilitating further improvement amongst expert sports performers and musicians – people who have already achieved elite status (Toner and Moran, in press). This evidence suggests that expert performers in motor domains (e.g., sport, music) can strategically deploy conscious attention to alternate between different modes of bodily awareness (reflective and pre-reflective) during performance. Extrapolating from this phenomenon, the current paper considers how a novel theoretical approach (adapted from Sutton, McIlwain, Christensen, and Geeves, 2011) could help researchers to elucidate some of the cognitive mechanisms mediating continuous improvement amongst expert performers.